René Girard, unlikely apologist: mimetic theory and fundamental theology - Kaplan, Grant (University of Notre Dame Press, 2016)
Mimetic theory as heuristic -- Mimetic theory and rational faith -- Mimetic theory and the theology of revelation -- Realizing a mimetic theology of religion -- Imagining a mimetic ecclesiology -- Trajectories of modernity: Girard and Taylor in conversation -- Mimetic theory and atheism -- One final apology.